Hollow silicon-carbon microspheres of porous carbon layer, and preparation method and application thereof

CN118529733BActive Publication Date: 2026-10-20IBIH ADVANCED MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310142600.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2026-10-20
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

[0004]现有技术多采用纳米硅颗粒进行包覆处理,步骤繁琐,且包覆存在不均匀,团聚的现象

Benefits of technology

[0018](1)本发明提供的采用溶胶凝胶的方法能够实现中空微球的制备和碳源的包覆,操作简便,且试剂可回收循环使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118529733B_ABST
    Figure CN118529733B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, and discloses a porous carbon layer hollow silicon-carbon microsphere and a preparation method and application thereof. The method comprises the following steps: (1) in the presence of water and ethanol, a silicon source is formed into a ball in the presence of an alkaline substance and a surfactant, to obtain product I with an average particle size of 50-900 nm; (2) the product I, a phenolic compound and an aldehyde compound are subjected to a contact reaction to obtain product II; (3) the product II is subjected to solid-liquid separation, and the obtained solid phase is subjected to washing and drying to obtain product III; and (4) the product III and a metal reducing agent are subjected to an oxidation-reduction reaction in an inert atmosphere. When the porous carbon layer hollow silicon-carbon microsphere prepared by the method is used as a battery negative electrode material, the electrochemical performance of the battery negative electrode material is stable, the cycle period is long, and the specific capacity is large.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to hollow silicon-carbon microspheres with porous carbon layers, their preparation methods, and applications. Background Technology

[0002] Improving the energy density of lithium-ion batteries to meet the growing demand for power batteries has become a hot research topic.

[0003] Silicon possesses a very high specific capacity and a suitable voltage plateau; its specific capacity is almost ten times that of the theoretical specific capacity of natural graphite, making it a promising anode material. However, it exhibits significant volume changes during charge and discharge, leading to material pulverization, structural collapse, and unstable specific capacity with severe degradation during charge-discharge cycles. Therefore, it is necessary to find ways to mitigate the volume expansion of silicon anode materials.

[0004] Existing technologies mostly employ nano-silicon particles for coating, a process that is cumbersome and prone to uneven coating and agglomeration. For example:

[0005] CN110660987A discloses a boron-doped hollow silicon spherical particle / graphitized carbon composite material, its preparation method, and its uses. The preparation method includes: (1) preparing solid silicon dioxide spherical particles; (2) preparing hollow silicon dioxide spherical particles; (3) preparing boron-doped hollow silicon spherical particles; and (4) preparing the boron-doped hollow silicon spherical particle / graphitized carbon composite material.

[0006] CN103988350A discloses a negative electrode active material for lithium secondary batteries and its preparation method. The preparation method includes: treating silicon polymer particles with a metal chloride solution to prepare silicon polymer particles with a metal catalyst loaded on their surface; dispersing the silicon polymer particles with the metal catalyst loaded on their surface in a plating bath filled with a plating solution containing metal ions for phosphorus-based alloys and phosphoric acid; heating the bath to form silicon polymer particles coated on a phosphorus (P)-based alloy surface; and carbonizing the silicon polymer particles coated on the phosphorus (P)-based alloy surface by heat treatment in a reducing atmosphere.

[0007] CN106145083A discloses a spherical hollow carbon shell composite material, its preparation method, and its application. The preparation method includes: calcining a metal source material or alloy source material together with a carbon source at high temperature; then, through oxidation, sulfidation, acid dissolution and replacement, or compound substitution steps, to obtain the spherical hollow carbon shell composite material.

[0008] The oxidation step includes oxidizing the calcined product in air or oxygen to form an oxide of a metal or alloy; the sulfidation step includes forming a sulfide of a metal or alloy from the high-temperature calcined product in a sulfur environment; the acid dissolution and replacement step includes washing the high-temperature calcined product with an acid solution to dissolve the carbon shell of the metal or alloy, or the oxide or sulfide of the metal or alloy, and then injecting elemental silicon or sulfur, or a compound of silicon or sulfur; the compound replacement step includes calcining elemental sulfur and the oxide of the metal or alloy together to replace the oxygen in the oxide of the metal or alloy with sulfur to obtain a sulfide. Summary of the Invention

[0009] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and to provide a silicon-carbon composite material that can buffer the volume expansion of silicon anode materials and has stable electrochemical performance when used as a battery anode material.

[0010] To achieve the above objectives, a first aspect of the present invention provides a method for preparing hollow silicon-carbon microspheres with porous carbon layers, the method comprising:

[0011] (1) In the presence of water and ethanol, and in the presence of alkaline substances and surfactants, silicon source was sphere-formed to obtain product I with an average particle size of 50-900 nm.

[0012] (2) The product I, phenolic compound and aldehyde compound are subjected to a contact reaction to obtain product II; the contact reaction conditions include: the reaction is carried out under stirring conditions, the stirring speed is 100-1000 rpm, the time is 2-18 h, and the temperature is 35-80℃; the molar ratio of the phenolic compound and the aldehyde compound is 1:1.5-3.

[0013] (3) The product II is subjected to solid-liquid separation, and the obtained solid phase is washed and dried to obtain product III;

[0014] (4) Under an inert atmosphere, the product III and the metal reducing agent are subjected to an oxidation-reduction reaction.

[0015] A second aspect of the present invention provides hollow silicon-carbon microspheres with porous carbon layers prepared by the method described in the first aspect above.

[0016] A third aspect of the present invention provides the application of hollow silicon-carbon microspheres with porous carbon layers as described in the second aspect above in battery anode materials.

[0017] The solution provided by this invention has at least the following advantages over the prior art:

[0018] (1) The sol-gel method provided by the present invention can realize the preparation of hollow microspheres and the coating of carbon source. The operation is simple and the reagents can be recycled.

[0019] (2) The method provided by the present invention can achieve uniform coating and the pore structure of the carbon layer is adjustable.

[0020] (3) When the hollow silicon carbon microspheres with porous carbon layers prepared by the method provided in this invention are used as battery anode materials, their electrochemical performance is stable, such as long cycle time, large specific capacity and high coulombic efficiency. Attached Figure Description

[0021] Figure 1 This is a SEM image of the hollow silicon-carbon microspheres with porous carbon layers prepared in Example 1 of this invention;

[0022] Figure 2 This is a characterization diagram of the electrochemical performance of hollow silicon-carbon microspheres with porous carbon layers prepared in Example 1 of the present invention. Detailed Implementation

[0023] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0024] As previously described, a first aspect of the present invention provides a method for preparing hollow silicon-carbon microspheres with porous carbon layers, the method comprising:

[0025] (1) In the presence of water and ethanol, and in the presence of alkaline substances and surfactants, silicon source was sphere-formed to obtain product I with an average particle size of 50-900 nm.

[0026] (2) The product I, phenolic compound and aldehyde compound are subjected to a contact reaction to obtain product II; the contact reaction conditions include: the reaction is carried out under stirring conditions, the stirring speed is 100-1000 rpm, the time is 2-18 h, and the temperature is 35-80℃; the molar ratio of the phenolic compound and the aldehyde compound is 1:1.5-3.

[0027] (3) The product II is subjected to solid-liquid separation, and the obtained solid phase is washed and dried to obtain product III;

[0028] (4) Under an inert atmosphere, the product III and the metal reducing agent are subjected to an oxidation-reduction reaction.

[0029] Preferably, the contact reaction is carried out under stirring conditions, with a stirring speed of 100-500 rpm, a time of 5-18 h, and a temperature of 50-70°C. The inventors of this invention have found that, under this preferred condition, the microspheres obtained by the method of this invention exhibit higher specific capacity and capacity retention when used as battery anode materials.

[0030] Preferably, the weight ratio of water to ethanol is 0.4-7:1. More preferably, the weight ratio of water to ethanol is 1-4:1.

[0031] In a preferred embodiment, based on the total amount of water and ethanol used, the amount of surfactant used is 0.1-5 wt%, and the amount of silicon source used is 0.2-10 wt%.

[0032] Preferably, the amount of alkaline substance used results in an initial reaction system pH of 8-9.5. The inventors of this invention have discovered that, under this preferred condition, the microspheres obtained by the method of this invention exhibit higher specific capacity, coulombic efficiency, and capacity retention when used as battery anode materials.

[0033] Preferably, the weight ratio of the silicon source to the phenolic compound is 1:0.2-1.5. More preferably, the weight ratio of the silicon source to the phenolic compound is 1:0.4-0.8.

[0034] In a preferred embodiment, the weight ratio of product III to the metal reducing agent is 1:0.1-1. More preferably, the weight ratio of product III to the metal reducing agent is 1:0.2-0.5. The inventors of this invention have found that, in this preferred embodiment, the microspheres obtained by the method of this invention exhibit higher specific capacity, coulombic efficiency, and capacity retention when used as a battery anode material.

[0035] According to a preferred embodiment, the conditions for pellet formation include: stirring at a speed of 100-1000 rpm for 2-14 hours and at a temperature of 35-45°C.

[0036] It should be noted that the present invention does not impose any particular limitations on the methods of solid-liquid separation and washing. Those skilled in the art can make selections based on known technical means in the art. The following text of the present invention provides a preferred specific embodiment, which should not be construed as a limitation of the present invention.

[0037] According to another preferred embodiment, the drying conditions include a temperature of 60-80°C and a time of 3-8 hours.

[0038] Preferably, the conditions for the redox reaction include: a temperature of 600-800℃ and a time of 1-5h.

[0039] Preferably, the alkaline substance is selected from at least one of ammonia, sodium bicarbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

[0040] Preferably, the critical micelle concentration (CMC) of the surfactant is <10. -2 mol / L. More preferably, the surfactant is selected from at least one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecyl sulfonate.

[0041] Preferably, the silicon source is selected from at least one of tetraethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, and methyltriethoxysilane.

[0042] Preferably, the metal reducing agent is selected from at least one of magnesium, aluminum, zinc, and iron.

[0043] In a preferred embodiment, the phenolic compound is selected from at least one of hydroquinone, catechol, resorcinol, and phenol.

[0044] Preferably, the aldehyde compound is selected from at least one of formaldehyde, acetaldehyde, propionaldehyde, and glyoxal.

[0045] To obtain a uniform and complete spherical structure, the present invention provides a particularly preferred embodiment in step (1).

[0046] (i) A first mixture of water, ethanol, an alkaline substance and a surfactant is obtained to obtain mixture I;

[0047] (ii) Mix the mixture I with a silicon source for a second time to obtain product I.

[0048] Preferably, the conditions for the first mixing include: being carried out under stirring conditions, with a stirring speed of 100-1000 rpm, a time of 0.2-2 h, and a temperature of 35-45 °C.

[0049] Preferably, the conditions for the second mixing include: being carried out under stirring conditions, with a stirring speed of 100-1000 rpm, a time of 2-12 h, and a temperature of 35-45 °C.

[0050] As previously stated, a second aspect of the present invention provides hollow silicon-carbon microspheres with porous carbon layers prepared by the method described in the first aspect.

[0051] As previously stated, a third aspect of the present invention provides the application of hollow silicon-carbon microspheres with porous carbon layers as described in the second aspect above in battery anode materials.

[0052] The present invention will be described in detail below through examples.

[0053] In the following examples, unless otherwise specified, all raw materials used were commercially purchased.

[0054] raw material:

[0055] Carboxymethyl cellulose: grade CMC2200, purchased from Youqia (Shanghai) International Trading Co., Ltd.

[0056] Styrene-butadiene latex: Grade S029, purchased from Kingmax Power Technology Co., Ltd.

[0057] Example 1

[0058] (1) Deionized water, anhydrous ethanol, 0.5 wt% ammonia water, and sodium dodecyl sulfate (CMC 9 × 10⁻⁶) were added. -3 The mixture was first mixed with mol / L to obtain mixture I;

[0059] The conditions for the first mixing are: the mixture is carried out under stirring conditions, with a stirring speed of 200 rpm, a time of 1 hour, and a temperature of 40°C.

[0060] The weight ratio of water to ethanol is 2:1;

[0061] The amount of alkaline substance used resulted in an initial pH of 8.5 in the reaction system.

[0062] Mixture I was mixed with methyl orthosilicate a second time to obtain product I with an average particle size of 200 nm;

[0063] The second mixing conditions are: carried out under stirring conditions, with a stirring speed of 200 rpm, a time of 10 h, and a temperature of 40 °C;

[0064] Based on the total amount of water and ethanol used, the amount of surfactant used was 1 wt%, and the amount of silicon source used was 0.4 wt%.

[0065] (2) Product I, resorcinol and formaldehyde are reacted to obtain product II;

[0066] The conditions for the contact reaction included: it was carried out under stirring at a speed of 300 rpm for 16 hours and at a temperature of 60°C.

[0067] The molar ratio of phenolic compounds to aldehyde compounds is 1:2;

[0068] The weight ratio of silicon source to phenolic compound is 1:0.4;

[0069] (3) Filter product II and wash the obtained solid phase twice alternately with deionized water and anhydrous ethanol, and dry it to obtain product III;

[0070] The drying conditions were: temperature 70℃, time 6 hours;

[0071] (4) Under a nitrogen atmosphere, product III and magnesium were subjected to a redox reaction to prepare microspheres Q1;

[0072] The weight ratio of product III to the metal reducing agent is 1:0.3;

[0073] The conditions for the redox reaction are: temperature 700℃ and time 3h.

[0074] Example 2

[0075] This embodiment uses a method similar to that of Embodiment 1, except that:

[0076] In step (1), sodium dodecyl sulfate is replaced with hexadecyltrimethylammonium bromide (CMC is 9.2 × 10⁻⁶). - 4 (mol / L), and adjust the dosage accordingly;

[0077] Replacing methyl orthosilicate with methyltriethoxysilane; thus

[0078] Based on the total amount of water and ethanol used, the amount of surfactant used was 0.5 wt%, and the amount of silicon source used was 0.4 wt%; the average particle size of product I was 150 nm.

[0079] All other conditions were the same as in Example 1, and microspheres Q2 were prepared.

[0080] Example 3

[0081] This embodiment uses a method similar to that of Embodiment 1, except that:

[0082] In step (2), the temperature in the contact reaction was adjusted to 80°C, and the other conditions were the same as in Example 1, and microspheres Q3 were prepared.

[0083] Example 4

[0084] This embodiment uses a method similar to that of Embodiment 1, except that:

[0085] In step (1), the amount of ammonia was adjusted so that the pH value of the initial reaction system was 10 and the average particle size of product I was 900 nm; the other conditions were the same as in Example 1, and microspheres Q4 were prepared.

[0086] Example 5

[0087] This embodiment uses a method similar to that of Embodiment 1, except that:

[0088] In step (4), the amount of magnesium was adjusted so that the weight ratio of product III to metal reducing agent was 1:0.05. All other conditions were the same as in Example 1, and microspheres Q5 were prepared.

[0089] Comparative Example 1

[0090] This comparative example was conducted using a method similar to that of Example 1, except that:

[0091] In step (1), anhydrous ethanol was replaced by anhydrous propanol at the same weight, and all other conditions were the same as in Example 1, and microspheres DQ1 were prepared.

[0092] Comparative Example 2

[0093] This comparative example was conducted using a method similar to that of Example 1, except that:

[0094] In step (1), sodium dodecyl sulfate is replaced by potassium laurate (CMC is 1.25 × 10⁻⁶) by weight. -2 The average particle size of product I was 1200 nm (mol / L); all other conditions were the same as in Example 1, and microspheres DQ2 were prepared.

[0095] Comparative Example 3

[0096] This comparative example was conducted using a method similar to that of Example 1, except that:

[0097] In step (2), the stirring speed in the contact reaction was adjusted to 1100 rpm, and the other conditions were the same as in Example 1, and microspheres DQ3 were prepared.

[0098] Comparative Example 4

[0099] This comparative example was conducted using a method similar to that of Example 1, except that:

[0100] In step (2), the amount of resorcinol was adjusted so that the molar ratio of phenolic compounds to aldehyde compounds was 1:1. All other conditions were the same as in Example 1, and microspheres DQ4 were prepared.

[0101] Comparative Example 5

[0102] This comparative example was conducted using a method similar to that of Example 1, except that:

[0103] In step (4), magnesium was replaced by hydrogen gas by weight, and all other conditions were the same as in Example 1, and microspheres DQ5 were prepared.

[0104] Test case

[0105] The microspheres prepared in the examples and comparative examples were used as battery active materials. The microspheres, conductive agent (Super P) and binder (carboxymethyl cellulose (CMC) + styrene-butadiene latex (SBR, m / m = 1:1) were dissolved in N-methylpyrrolidone (NMP) at a mass percentage of 8:1:1. The solution was coated on a copper foil current collector and vacuum dried to obtain an electrode. The counter electrode used a lithium metal sheet. The electrolyte was 1.2 mol / L LiPF6 / (ethylene carbonate (EC) + dimethyl carbonate (DMC) + diethyl carbonate (DEC) (v / v / v = 1:1:1)) and a Celgard 2400 separator. The cells were assembled into coin cells. 100 constant current charge-discharge tests were conducted at a current density of 0.1C and a test temperature of 25℃. The specific results are shown in Table 1.

[0106] Table 1

[0107] Example 1 810 86.5 98.2 Example 2 795 87.2 97.8 Example 3 805 86.8 97.6 Example 4 720 78.7 93.4 Example 5 600 75.1 85.7 Comparative Example 1 560 71.6 70.8 Comparative Example 2 535 70.3 80.3 Comparative Example 3 581 72.5 82.1 Comparative Example 4 610 73.4 81.5 Comparative Example 5 590 71.8 75.3

[0108] As can be seen from the results in Table 1, when hollow silicon-carbon microspheres with porous carbon layers prepared by the method provided in this invention are used as battery anode materials, their electrochemical performance is stable, their cycle life is long, and their specific capacity is large.

[0109] Figure 1 This is a SEM image of the hollow silicon-carbon microspheres with porous carbon layers prepared in Example 1 of this invention. The SEM images of the hollow silicon-carbon microspheres with porous carbon layers prepared in the other embodiments of this invention are similar. The SEM image of the hollow silicon-carbon microspheres with porous carbon layers in Example 1 is provided as an example in this invention.

[0110] from Figure 1 It can be seen that the surface of the microspheres has a porous structure and good particle size uniformity.

[0111] Figure 2 This is a characterization diagram of the electrochemical performance of the hollow silicon-carbon microspheres with porous carbon layers in Example 1 of this invention. Figure 2 The results show that the microspheres, as the anode material of the battery, have an initial specific capacity of up to 810 mAh / g, and the capacity retention rate is high after 100 cycles, indicating good electrochemical cycling stability.

[0112] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing hollow silicon-carbon microspheres with porous carbon layers, characterized in that, The method includes: (1) In the presence of water and ethanol, and in the presence of alkaline substances and surfactants, silicon source is spheroidized to obtain product I with an average particle size of 50-900 nm; the amount of alkaline substances used makes the pH value of the initial reaction system 8-9.5; (2) The product I, phenolic compound and aldehyde compound are subjected to a contact reaction to obtain product II; the contact reaction conditions include: the reaction is carried out under stirring conditions, the stirring speed is 100-1000 rpm, the time is 2-18 h, and the temperature is 35-80 °C; the molar ratio of the phenolic compound and the aldehyde compound is 1:1.5-3. (3) The product II is subjected to solid-liquid separation, and the obtained solid phase is washed and dried to obtain product III; (4) Under an inert atmosphere, the product III and the metal reducing agent are subjected to an oxidation-reduction reaction.

2. The method according to claim 1, wherein, The weight ratio of water to ethanol is 0.4-7:1; and / or, Based on the total amount of water and ethanol used, the amount of surfactant used is 0.1-5 wt%, and the amount of silicon source used is 0.2-10 wt%.

3. The method according to claim 1 or 2, wherein, The weight ratio of the silicon source to the phenolic compound is 1:0.2-1.5; and / or, The weight ratio of product III to the metal reducing agent is 1:0.1-1.

4. The method according to claim 1 or 2, wherein, The conditions for pellet formation include: stirring at a speed of 100-1000 rpm for 2-14 hours, and at a temperature of 35-45°C; and / or, The drying conditions include a temperature of 60-80℃ and a time of 2-8 hours.

5. The method according to claim 1 or 2, wherein, The conditions for the redox reaction include: a temperature of 600-800℃ and a time of 1-5h.

6. The method according to claim 1 or 2, wherein, The alkaline substance is selected from at least one of ammonia, sodium bicarbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate; and / or, The critical micelle concentration of the surfactant is <10. -2 mol / L.

7. The method according to claim 1 or 2, wherein, The silicon source is selected from at least one of tetraethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, and methyltriethoxysilane; and / or, The metal reducing agent is selected from at least one of magnesium, aluminum, zinc, and iron.

8. The method according to claim 1 or 2, wherein, The phenolic compound is selected from at least one of hydroquinone, catechol, resorcinol, and phenol; and / or, The aldehyde compounds are selected from at least one of formaldehyde, acetaldehyde, propionaldehyde, and glyoxal.

9. Hollow silicon-carbon microspheres with porous carbon layers prepared by the method according to any one of claims 1-8.

10. The application of hollow silicon-carbon microspheres with porous carbon layers as described in claim 9 in battery anode materials.

Citation Information

Patent Citations

  • Anode active material for lithium secondary batteries and method for manufacturing same

    CN103988350A

  • Spherical hollow carbon shell preparation method, and spherical hollow carbon shell and applications thereof

    CN106145083A

  • Boron-doped hollow silicon spherical particle / graphitized carbon composite material and preparation method thereof

    CN110660987A

  • Composite negative electrode material, preparation method thereof and lithium ion battery

    CN114551886A